EXPLORING EFL STUDENTS’ PERSPECTIVE ON ARTIFICIAL INTELLIGENCE IN SUPPORTING WRITING PROCESS - Sihombing, Rizqie Ramadhan (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2025)
This study was aimed to explore learners’ perspective of using artificial intelligence. The respondents of this study were 15 learners who had completed the academic writing course. The technique of collecting data used was a semi structured interview method to EFL learners who had experience using AI technology to help their writing assignments. The research design used in this study was qualitative. The results revealed that all of students using AI in helping their writing assignment. The findings showed that the artificial intelligence variation used by the learners were ChatGPT, Grammarly, DeepLWriting, Quillbot, Bing Translator, Gemini and POE to help them doing their writing assignments. However, the EFL students still found the result of writing was inaccurate, so they cross referenced them manually and sometimes used other AI tools to refine the writing. The results utilization of Artificial Intelligence in supporting of their writing assignment indicated students’ positive perspective of utilizing Artificial Intelligence in composing their writing assignments influences the efficacy of their written work.